PENGATURAN PENGELOLAAN HUTAN DI ATAS TANAH HAK MILIK DI DESA TENGANAN PEGRINGSINGAN - I Gede Mahendra; I Made Arya Utama (Kertha Negara : Journal Ilmu Hukum, 2015)
Forest environmental crisis is one of the environmental issues that are currently getting a lot of attention. Thanks to local knowledge in forest management PegringsinganTenganan village became a reference in maintaining the forest environment in Indonesia. By using method of normative, formulation of the problem that occurs how does the setting and the rights of the forest management. Can be concluded that regulation and management of forest plants in the village of Tenganan Pegringsingan awig-awig incorporated into the traditional village of Tenganan Pegringsingan,so the forest plants and grow well maintained and sustainable.